The Process of Investigating Planetary Transits in Photometric Light Curves from TESS - Bittencourt, Mariana; Bom, Clécio; Silva, Stela (Cadernos de Astronomia, 2026)
In exoplanetary astronomy, the transit method, based on the analysis of variations in stellar brightness due to the passage of the planet in front of its host star and recorded in light curves, is one of the main techniques for detecting planets outside the Solar System, responsible for most of the current discoveries. In this work, we use data obtained by the Transiting Exoplanet Survey Satellite (TESS) and study the use of a methodology for the processing, detection, and validation of transit signals in TESS photometric data, involving the adaptation of codes, the implementation of analysis pipelines, and the verification of candidates based on astrophysical criteria, with a view to identifying new exoplanets.